The GPCR antagonist PPTN synergizes with caspofungin providing increased fungicidal activity against Aspergillus fumigatus - Thaila Fernanda dos Reis; Endrews Delbaje; Camila Figueiredo Pinzan; Rafael Bastos; Suzanne Ackloo; Sara Fallah; Bradley Laflamme; Nicole Robbins; Leah E. Cowen; Gustavo H. Goldman (Microbiology Spectrum)
ABSTRACT Fungal pathogens pose a serious threat to human health, with Candida and Aspergillus spp. representing some of the most significant opportunistic invaders. Aspergillus fumigatus causes aspergillosis, one of the most prevalent fungal diseases of humans. There is a limited number of drugs available to combat these infections, and antifungal drug resistance is on the rise. In this manuscript, we show 4-[4-(4-Piperidinyl) phenyl]-7-[4-(-(trifluoromethyl) phenyl]-2-naphthalenecarboxylic acid (PPTN), a highly specific antagonist of the human P2Y14 receptor, is a promising antifungal adjuvant against diverse fungal pathogens. PPTN interacts with caspofungin (CAS), ibrexafungerp, voriconazole (VOR), and amphotericin against A. fumigatus CAS- and VOR-resistant clinical isolates, and also CAS against Candida spp and Cryptococcus neoformans. The combination of PPTN and CAS increases cell death in A. fumigatus. In the model yeast Saccharomyces cerevisiae, heterozygous deletion of genes involved in chromatin remodeling results in PPTN hypersensitivity, and in A. fumigatus, PPTN can have increased fungicidal activity when combined with the histone deacetylase inhibitor trichostatin A and the DNA methyltransferase inhibitor 5-azacytidine. Finally, PPTN has reduced toxicity to human immortalized cell lineages and partially clears A. fumigatus conidia infection in A549 pulmonary epithelial cells. Our results indicate that PPTN is a novel adjuvant antifungal drug against fungal diseases caused by A. fumigatus and Candida spp.IMPORTANCEInvasive fungal infections have a high mortality rate, causing more deaths annually than tuberculosis or malaria. Aspergillus fumigatus is the main etiological agent of aspergillosis, one of the most prevalent and deadly fungal diseases. There are few therapeutic options for treating this disease, and treatment commonly fails due to host complications or the emergence of antifungal resistance. Drug repurposing, where existing drugs are deployed for other clinical indications, has increasingly been used in the process of drug discovery. Here, we show that 4-[4-(4-Piperidinyl) phenyl]-7-[4-(-(trifluoromethyl) phenyl]-2-naphthalenecarboxylic acid (PPTN), a highly specific antagonist of the human P2Y14 receptor, when combined with caspofungin (CAS), ibrexafungerp, voriconazole (VOR), and amphotericin can increase the fungicidal activity against not only A. fumigatus CAS- and VOR-resistant clinical isolates but also CAS against Candida spp.